2020
DOI: 10.1007/s41999-020-00427-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral health on prognosis of older multimorbid inpatients: the 6-month follow up MPI oral health study (MPIOH)

Abstract: Aim To identifying tools for the reliable and systematic evaluation of oral health in older inpatients as well as to addressing the association between oral health and patients' prognosis as measured by the Comprehensive Geriatric Assessment (CGA)-based Multidimensional Prognostic Index (MPI). Findings Valid oral health examinations can be performed in older inpatients and are associated with individual multidimensional prognosis. Message Oral health should be assessed and incorporated into clinical decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…All three observational papers displayed a link between poor OH and an increased risk of mortality, Maeda and Mori, 25 Noetzel et al 26 and Bartoli et al 27 The non-randomised control trial by Shiraishi et al 28 showed that OH interventions by a dental hygienist (DH) were associated with lower in-hospital mortality. These results were echoed in the systematic review by Sjögren et al, 29 where it was found that the mortality risk from hospital-acquired pneumonia (HAP) improved with dental personnel OC interventions but did not improve when nursing personnel provided OC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three observational papers displayed a link between poor OH and an increased risk of mortality, Maeda and Mori, 25 Noetzel et al 26 and Bartoli et al 27 The non-randomised control trial by Shiraishi et al 28 showed that OH interventions by a dental hygienist (DH) were associated with lower in-hospital mortality. These results were echoed in the systematic review by Sjögren et al, 29 where it was found that the mortality risk from hospital-acquired pneumonia (HAP) improved with dental personnel OC interventions but did not improve when nursing personnel provided OC.…”
Section: Resultsmentioning
confidence: 99%
“…Noetzel et al 26 found that poorer OH and the multidimensional prognostic index (MPI) were independently associated. Fifty percent of MPI 3 patients had died at the six-month follow-up, 23% of MPI 2 and 12.5% of MPI 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that low levels of oral health are associated with poor health outcomes, and the WHO has suggested that oral health is an essential determinant of quality of life, overall health, and well-being. 43 The present study conducted a comprehensive analysis of oral health assessment tools for older individuals by including 19 research via a scoping review. The primary objective was to elucidate the psychosocial characteristics of these tools, therefore establishing a theoretical foundation for the evaluation of oral health in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the urgently needed improvement in communication between nursing homes and external dentists, intraoral photographs can be used as standard in other situations, such as communication between dentists, practice teams and their patients and interprofessional exchanges between doctors and dentists. For years, it has been emphasised that communication between dentists and general practitioners must be intensified, especially for patients in need of care 26,27 . Since this communication often fails due to organisational time constraints, smartphone photographs would be a further possibility to open up low‐threshold communication channels.…”
Section: Discussionmentioning
confidence: 99%
“…For years, it has been emphasised that communication between dentists and general practitioners must be intensified, especially for patients in need of care. 26,27 Since this communication often fails due to organisational time constraints, smartphone photographs would be a further possibility to open up low-threshold communication channels. In particular, if patients are not yet in an inpatient facility but still need care at home, smartphone photography offers a practical form of communication that would help the patient and their support environment to maintain contact with their dentist.…”
Section: Discussionmentioning
confidence: 99%